2014
DOI: 10.3109/00016357.2014.956333
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Demirjian method for dental age estimation in western Turkish children

Abstract: The applicability of the Demirjian method is not suitable for western Turkish children and western Turkish children have a lower degree of dental maturity than that observed in the eastern, northeastern and northern Turkish subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
2
22
1
4
Order By: Relevance
“…The dental age estimations performed using the Demirjian method in Turkish children living in different geographical locations usually overestimated chronological age (9,11,13,14). Willems et al (10) published their revised maturity scores almost 25 years after Demirjian et al's study (8).…”
Section: Discussionmentioning
confidence: 99%
“…The dental age estimations performed using the Demirjian method in Turkish children living in different geographical locations usually overestimated chronological age (9,11,13,14). Willems et al (10) published their revised maturity scores almost 25 years after Demirjian et al's study (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults. In previous studies conducted in Turkish populations, it has been reported that dentition shows gender differentiation, with that in females preceding that in males [13][14][15]17,19,21]. Karadayi et al [19] described that this difference was usually in only one stage and not in all teeth.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies in the literature evaluate the applicability of Demirjian method for Turkish population between 2010 and 2015 [13][14][15][17][18][19]. In all studies, the applicability of Demirjian method is not suitable for Turkish population [14,15,18] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all studies, the applicability of Demirjian method is not suitable for Turkish population [14,15,18] (Table 3). Therefore, in the present study, modified Demirjian method is adapted to the Turkish population, (Figures 1-3).…”
Section: Discussionmentioning
confidence: 99%